Using ultrasonic sensors to measure liquid level and density in computerized information and measurement systems - Yu.O. Podchashynskyi; O.S. Ishchenko (Технічна інженерія)
Modern industry places strict requirements on continuous monitoring and automation of processes involving liquid media. Precise control of liquid level and density directly affects the safety, efficiency and environmental performance of production. Therefore, the introduction of reliable measuring devices capable of operating in real time and withstanding difficult operating conditions is of strategic importance for various industries, from the petrochemical to the pharmaceutical and food industries.